Global burden of ovarian cancer attributable to high body mass index among women of childbearing age from 1990 to 2021 and projections to 2050: a systematic analysis for the global burden of disease study 2021 - Chen, Hongxi; Lin, Zidan; Chen, Jing; He, Shanyang (Frontiers in Oncology, 2025)
BackgroundOvarian cancer (OC) remains a lethal gynecologic cancer marked by substantially reduced 5-year survival probabilities. Elevated BMI (≥25 kg/m²) constitutes a progressively recognized OC risk determinant mediated by chronic inflammatory states and metabolic pathway perturbations. Leveraging GBD 2021 repositories, this investigation quantified high BMI-attributable ovarian cancer burden trajectories among reproductive-age women (WCBA, 15–49 years) worldwide.MethodsLeveraging GBD 2021 repositories, we evaluated worldwide OC burden mediated by elevated BMI across women of childbearing age (WCBA) during 1990-2021. Evaluated metrics comprised deaths, DALYs, YLDs, YLLs, and ASR (EAPC-based trend analysis). ARIMA and Exponential Smoothing models generated 2050 burden projections.ResultsFrom 1990 to 2021, the global burden of OC attributable to high BMI increased significantly. In 2021, there were 17,344 deaths (95% UI: 4,141–30,810) and 477,248 DALYs (95% UI: 113,449–840,002) among WCBA. The ASMR rose from 0.32 (95% UI: 0.07–0.61) to 0.38 (95% UI: 0.09–0.67) per 100,000 (EAPC: 1.03, 95% CI: 0.85–1.21). The ASDR increased from 8.72 (95% UI: 1.78–16.41) to 10.56 (95% UI: 2.50–18.57) per 100,000 (EAPC: 1.09, 95% CI: 0.93–1.25). The burden peaked in the 45–49 age group, with 995 deaths and 44,223 DALYs. High SDI regions had the highest ASMR (0.57, 95% UI: 0.14–1.01) and ASDR (15.13, 95% UI: 3.79–26.82). Projections indicate a continued increase in the OC burden attributable to high BMI by 2050, with the ASMR reaching 0.43 (95% HDI: 0.40–0.46) and the ASDR reaching 12.28 (95% HDI: 11.58–12.98).ConclusionThis study highlights the escalating global burden of OC attributable to high BMI among WCBA, particularly in high SDI regions. This investigation delineates progressively intensifying worldwide OC burden mediated by elevated BMI in WCBA, disproportionately affecting high SDI territories.